2014
DOI: 10.1590/0103-8478cr20130747
|View full text |Cite
|
Sign up to set email alerts
|

Dois diluentes comerciais na criopreservação de espermatozoides do epidídimo de touros

Abstract: A recuperação e a criopreservação de espermatozoides do epidídimo constituem alternativas viáveis para a preservação de material genético de animais valiosos. O objetivo deste estudo foi comparar o desempenho de dois diluentes comerciais Botu-Bov® (BB)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
3
0
3
Order By: Relevance
“…Because the computerized software accepts only files in the AVI format, the videos were converted to AVI format and analyzed using the plugin settings indicated in the article by Giaretta et al (2017) and the configuration settings indicated in the articles by Hoflack et al (2007), Sellem et al, (2015) and Polo (2016). For each video, 30 frames were analyzed (131-160 frames), according to the method described by Bertol et al (2014) and Sellem et al (2015). To read the videos without interference, it was necessary to make some adjustments in the program (ImageJ).…”
Section: Methodsmentioning
confidence: 99%
“…Because the computerized software accepts only files in the AVI format, the videos were converted to AVI format and analyzed using the plugin settings indicated in the article by Giaretta et al (2017) and the configuration settings indicated in the articles by Hoflack et al (2007), Sellem et al, (2015) and Polo (2016). For each video, 30 frames were analyzed (131-160 frames), according to the method described by Bertol et al (2014) and Sellem et al (2015). To read the videos without interference, it was necessary to make some adjustments in the program (ImageJ).…”
Section: Methodsmentioning
confidence: 99%
“…The cryopreservation protocol in liquid nitrogen and the dilution with TRIS base-egg yolk are effective [8,23]. For bulls, the process consists of first sample centrifugation to separate the spermatozoa from other contaminants and the recovery medium.…”
Section: Cryopreservation Of Epididymal Spermmentioning
confidence: 99%
“…A utilização do sêmen bovino criopreservado apresenta vantagens em relação às demais formas de processamento pois possibilita a expansão da genética de diferentes touros mundialmente, além de atuar na prevenção da disseminação de doenças passíveis de transmissão por meio de monta natural. No entanto, o uso do sêmen criopreservado geralmente apresenta menores taxas de fertilidade em relação ao sêmen fresco (Bertol et al, 2014).…”
Section: Introductionunclassified
“…Os principais fatores envolvidos nessa queda de fertilidade são as mudanças de temperatura durante o processamento, o estresse osmótico e tóxico representado pela exposição aos crioprotetores e a formação e dissolução de cristais de gelo extracelulares (Oliveira et al, 2013;Bertol et al, 2014;Quan et al, 2016;Losano, 2016). Assim a sobrevivência do sêmen criopreservado, depende de agentes que presentes na composição do meio diluidor, crioprotetores, tornando-se um fator crucial para a preservação da integridade celular e sucesso da fertilização após o congelamento (Leite et al, 2011).…”
Section: Introductionunclassified
See 1 more Smart Citation